Analisis Persahabatan Dalam Drama All Of Us Are Dead - Ahmad Fauzi; Siti Nur Khabibah Romantika (Medio Jurnal Ilmu Komunikasi, 2023)
Netflix released a drama series entitled "All of Us Are Dead" which tells the story of a group of teenagers who are trying to save themselves from being chased by zombies that occur at their school. At first their friendship was established because of circumstances, but because they were often together made them closer and believed in each other, so they were willing to sacrifice themselves so that their friends could survive the zombies. The focus of the problem in this study is how the meaning of friendship in the drama all of us are dead with the aim of research to determine the meaning of friendship in the drama all of us are dead contained in episodes 1 and 2. In this study the researcher used a qualitative descriptive research type with the presentation of Charles semiotics Sanders Peirce and Aristotle's concept of friendship, and for data collection techniques, researchers used observation and documentation and the validity of the data used was a triangulation technique based on theory. This study analyzed 33 scenes in which 9 scenes were analyzed using Charles Sander Peirce's semiotics with the results of the study found 4 meanings of friendship, namely 1) togetherness, 2) caring, 3) cooperation, and 4) always being there under any circumstances. And 22 scenes grouped together based on Aristotle's notion of friendship, namely: 1) Friendship Based on Need or Utility (Utinity): Overcoming Fear and Doubt. 2) Friendship based on pleasure (Pleasure): A friendship between two people who share the same interests or jokes. 3) Friendship of Kindness or Virtue (Virtue): The friendship that exists between them becomes more and more intimate through trust, understanding and self-sacrifice. They do not hesitate to give advice and advice so that their friends will not be afraid or sad. they reinforce each other. The care shown through love and affection makes a person feel valued and cherished.